Implementation of the Joyful Learning Method to Enhance Student Participation in Aqidah Akhlaq Learning at Islamic Elementary Schools - Ghanimah Ghanimah; Nur Aisyah (Universitas Nurul Jadid, 2025)
This study aims to describe the implementation of the Joyful Learning method in enhancing student participation in the Aqidah Akhlaq (Islamic Creed and Morals) subject, identify the supporting and inhibiting factors, and analyze the results of the implementation at MI Miftahul Ulum and MI Sirajul Ulum Opo-Opo Krejengan Probolinggo. The main problem addressed is the low level of student activity and interest in Aqidah Akhlaq learning, often attributed to conventional teaching methods and a lack of engaging media. This research adopts a qualitative approach using a multi-site case study design. Data collection involved participatory observation, in-depth interviews (principals, teachers, and students), and documentation. The collected data were analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that: (1) The implementation of the Joyful Learning method was carried out through three main stages: planning (formulating objectives, selecting material, preparing lesson plans), execution (creating a fun atmosphere, utilizing educational games, songs, and storytelling), and evaluation (reflection and feedback). (2) The primary supporting factors include the teacher’s creativity and mastery of the method, the availability of innovative simple media, and full support from the school principal. Inhibiting factors include insufficient time allocation for detailed media preparation, limited school facilities and infrastructure, and the challenge of managing large, highly energetic classes. (3) The results of the implementation show a significant increase in student participation, evidenced by heightened enthusiasm, intrinsic motivation, and students' courage to ask questions, answer, and actively interact during the learning process, which positively impacts their understanding and internalization of Aqidah Akhlaq values.